Penerapan Fuzzy Inference System Tsukamoto dalam Menentukann Jumlah Produksi Tahu Pada Pabrik Alfaria KM 07 Kefamenanu - Hendrika Yeni Meti; Grandianus Seda Mada; Leonardus Frengky Obe (Journal of Mathematics Theory and Applications, 2022)
Tofu is a food that is familiar to the people of Indonesia, because it contains many benefits and the price is cheap. One of the tofu production businesses in Timor Tengah Utara Regency is Alfaria's Tofu Business. Since its inception of this factory until 2019, the factory has experienced an increase in the number of production, but since the Covid-19 in 2020, the number of production has became uncertain due to social restrictions imposed by the government. There are many ways that can be done to determine the optimum production number, one of which is by using the Tsukamoto Fuzzy Inference System (FIS). The application of this method aims to provide a solution on how to determine the number of tofu that will be produced based on the number of vinegar and soybean raw materials, the availability of wood as fuel, the number of demand and supply of tofu. Then to determine the level of accuracy of the method used, an error check is carried out by comparing the difference between the predicted data and the actual data using the Mean Absolute Percentage Error (MAPE). Based on the results of calculations with Tsukamoto FIS, the number of tofu that must be produced by the Alfaria Tofu Factory throughout 2021 with an accuracy level of 96.25% is obtained, so it can be concluded that Tsukamato FIS method is very good to be used as a method for predicting the number of production for the Alfaria Tofu Factory.